2020
DOI: 10.1136/jclinpath-2019-206235
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory characteristics of clozapine-treated patients with schizophrenia referred to a national immunodeficiency clinic reveals a B-cell signature resembling common variable immunodeficiency (CVID)

Abstract: AimsAn association between antibody deficiency and clozapine use in individuals with schizophrenia has recently been reported. We hypothesised that if clozapine-associated hypogammaglobulinaemia was clinically relevant this would manifest in referral patterns.MethodsRetrospective case note review of patients referred and assessed by Immunology Centre for Wales (ICW) between January 2005 and July 2018 with extraction of clinical and immunological features for individuals with diagnosis of schizophrenia-like ill… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
0
17
0
2
Order By: Relevance
“…Early recent research from one research group has found a reduction in immunoglobulin levels in patients taking clozapine, with a greater effect in those taking long-term treatment. 4143 These studies found clinically significant panhypogammaglobulinaemia and impaired vaccine responses in patients taking clozapine that were not fully explained by smoking or concurrent medication. 41 Reductions in pneumococcal-specific IgA and IgM were also observed.…”
Section: Pneumoniamentioning
confidence: 97%
See 1 more Smart Citation
“…Early recent research from one research group has found a reduction in immunoglobulin levels in patients taking clozapine, with a greater effect in those taking long-term treatment. 4143 These studies found clinically significant panhypogammaglobulinaemia and impaired vaccine responses in patients taking clozapine that were not fully explained by smoking or concurrent medication. 41 Reductions in pneumococcal-specific IgA and IgM were also observed.…”
Section: Pneumoniamentioning
confidence: 97%
“…4143 These studies found clinically significant panhypogammaglobulinaemia and impaired vaccine responses in patients taking clozapine that were not fully explained by smoking or concurrent medication. 41 Reductions in pneumococcal-specific IgA and IgM were also observed. 43 A longer duration of clozapine use was associated with a higher risk of hypogammaglobulinaemia (annual decline of 0.15 g/l).…”
Section: Pneumoniamentioning
confidence: 97%
“… 14 Pneumonia is a significant contributor to mortality in patients taking clozapine, 15 and early data from one group have suggested an effect of clozapine on levels of some immunoglobulins leading to a reversible immunodeficiency-like syndrome, which may correlate with the rate of infections. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Cette action passe en partie par une réduction des taux circulants des immunoglobulines (Ig) des trois classes [6]. L'hypogammaglobulinémie observée concerne également les Ig G spécifiques anti-haemophilus influenza et pneumocoques, pathogènes communs du tractus respiratoire.…”
unclassified
“…L'ampleur de l'action immunosuppressive de la clozapine est comparable à celle de l'association rituximab-methotrexate [7]. Elle est d'autant plus marquée que la durée de traitement par la clozapine est longue et ne semble pas être dose dépendante [6,7]. Il est toutefois important de souligner les nombreux rapports de cas, associant dose élevée de clozapine et infection sévère [8].…”
unclassified